Trade Flows and Trade Disputes - Bown, Chad P.; Reynolds, Kara M. (Springer, 2014)
This paper introduces a new data set and establishes a set of basic facts and patterns regarding the ‘trade’ that countries fight about under WTO dispute settlement. It characterizes the scope of products, as well as the levels of and changes to the trade values, market shares, volumes, and prices for those goods that eventually become subject to WTO litigation. The first result is striking heterogeneity in the level of market access at stake across disputes: e.g., 14% of cases over disputed import products feature bilateral trade that is less than $1 million per year, and another 15% feature bilateral trade that is more than $1 billion per year. Nevertheless, some strong patterns emerge from a more detailed examination of the data. Both high- and low-income complainants tend to suffer important losses in foreign market access in the products that ultimately become subject to dispute. Furthermore, while the respondent’s imposition of an allegedly WTO-inconsistent policy is associated with reductions, on average, to trade values, volumes and exporter-received prices, there is some evidence of differences in the size of these changes across both the different types of policies under dispute and the potential exporter country litigants. Finally, these different types of policies under dispute can have dissimilar trade effects for the complainant relative to other (non-complainant) exporters of the disputed product, and this is likely to affect the litigation allegiance of third countries.